Hepatotoxic Effect of Hydrogen Cyanamide (Dormex®) in Albino Rats and the Ameliorative Effect of Melatonin: Hepatotoxic effect of hydrogen cyanamide (Dormex) in albino rats and the ameliorative effect of melatonin - Mohammed, Amal; El Sayed, Ahmed Salah (International Journal of Medical Toxicology and Forensic Medicine, 2024)
Background: Hydrogen cyanamide (Dormex®) is used as a fertilizer sprayed on fruits, especially grapes to stimulate buds’ opening. It causes oxidative stress leading to hepatic, renal, and lung damage. Melatonin is derived primarily from the amino acid tryptophan, produced from the pineal gland, and has antioxidant effects. This study aimed to examine the effects of acute hydrogen cyanamide (Dormex®) exposure on the liver of albino rats and evaluate the biochemical and histological changes caused by Dormex® toxicity. Additionally, the study evaluated the potential ameliorative role of melatonin in these harmful effects. Methods: Forty adult male albino rats were divided into four groups; group I: Negative control, group II: Melatonin-treated (100 mg/kg/day), group III: Dormex®-treated (100 mg/kg) as a single dose, and group IV: Receiving melatonin (100 mg/kg/day)+Dormex® (100 mg/kg). After 24 hours, all animals were evaluated for liver enzymes (alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, and bilirubin), hepatic markers for oxidative stress (malondialdehyde (MDA), reduced glutathione (GSH), and superoxide dismutase (SOD)) and histopathological examination was done for hepatic tissues. Results: The Dormex®-treated group showed significantly elevated liver enzymes, elevated MDA, and decreased GSH and SOD. Histopathological examination revealed normal structure in groups 1 and 2 while group 3 showed several histopathological changes characterized by inflammation and hepatic necrosis. Administration of melatonin with Dormex® in group 4 caused a decrease in liver enzymes and MDA and an increase in GSH and SOD with improvement in liver histopathology. Conclusion: Melatonin showed an ameliorative effect and can be used as a protective agent against Dormex®-induced hepatic injury.